Pengaruh Kompetensi Aparatur dan Sistem Informasi terhadap Partisipasi Politik pada Pilkada COVID-19: Analisis SEM dan Model Skills Democracy - Afif Syarifudin Yahya (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the influence of Apparatus Competency and Information Systems on Community Political Participation in the Local Government Head Election during the COVID-19 pandemic era in Karawang Regency. The COVID-19 pandemic has posed significant challenges to democratic processes, particularly in maintaining voter participation while ensuring public health safety. Employing a mixed-methods approach combining quantitative and qualitative data with Structural Equation Modeling (SEM) analysis, this research analyzed data from 263 respondents across various election administrative units. The results indicate that: (1) Apparatus Competency does not have a significant positive effect on Community Political Participation (T-value = 1.01 < 1.96); (2) Information Systems have a significant positive effect on Community Political Participation (T-value = 2.78 > 1.96; path coefficient = 0.67). The combined contribution of both variables explains 76% of the variance in political participation. From these findings, the study proposes the Skills Democracy Model, emphasizing that digital information skills and organizational experience are critical determinants of democratic participation quality during pandemic conditions. These findings have significant implications for election governance reform and e-democracy development in Indonesia.